Mobilizing and Managing Public Forestry Revenue - Verhoeven, Marijn (World Bank, Washington, DC, 2019)
This paper considers the potential for improvements in forestry revenue management to complement other efforts toward sustainable forest management and to strengthen domestic resource mobilization. It describes forestry management as an extreme version of a classic principal-agent problem, which manifests itself in high levels of corruption, illegality, and revenue leakage at the country level. To address these challenges, the paper proposes that governments adopt a three-tiered sectoral planning process with an appropriately long time horizon, reflecting the length of forest life cycles and the uniqueness of the sector given forests’ status as a renewable natural resource providing essential public goods. Building on a sound planning process, the paper recommends mainstreaming attention to revenue-related issues throughout sectoral management by improving data availability, increasing transparency and stakeholder engagement, and implementing a robust revenue management system. It suggests a set of key revenue management components and institutional principles that can be applied to the local context as appropriate, with the aid of a questionnaire developed to help governments assess current strengths and weaknesses. These approaches may enable governments to improve decision making on land use, protect financial and physical resources that rightfully belong to the citizenry, and strengthen the rule of law in a sector often plagued by its abuse.